(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
in this article, it presents information on the development of the textile, sewing-knitting, leather-shoe and furry industries of light industry in the Republic, the expansion of the types and assortment of manufactured finished products, as well as the investment and export activities of Network Enterprises. The light industry is a crucial segment of global manufacturing that includes industries involved in the production of consumer goods, textiles, electronics, food processing, and other products essential to everyday life. This sector has seen significant growth and transformation, driven by technological innovations, increasing demand for sustainable practices, and the continuous evolution of global trade dynamics. The light industry plays a key role in providing employment, supporting economic development, and fostering international trade and cooperation.